Short-acting beta agonist, antibiotics, oral corticosteroid and association with mortality and cardiopulmonary events in patients with COPD: a retrospective cohort study in Alberta, Canada - Mohit Bhutani; Irvin Mayers; Arsh Randhawa; Manisha Talukdar; Suzanne McMullen; Phongsack Manivong; Aaron Gelfand (BMJ Open)
Objective The purpose of the study was to examine the association between short-acting beta agonist (SABA), antibiotic and oral corticosteroid (OCS) use and mortality and cardiopulmonary outcomes in chronic obstructive pulmonary disease (COPD).Design Retrospective cohort study using administrative health data from 1 April 2011 to 31 March 2020.Setting Alberta, Canada.Participants Patients ≥35 years old with COPD were identified using diagnostic codes.Primary and secondary outcome measures Patient characteristics included age, sex, geographical zone and comorbidities (as defined by the Charlson Comorbidity Index). Outcome variables included all-cause and COPD-related mortality. Outcomes were assessed in consecutive 90-day intervals, starting from cohort entry, paired with time-varying COPD-related medication history in the 1 year preceding each interval. Associations were modelled between mortality and SABA, antibiotic and OCS history, and between major adverse cardiac events (MACE) and cardiovascular disease (CVD) death and SABA history.Results Among 188 969 patients, dose–response effects were observed. Adjusting for covariates, rates were higher for patients with 6+ (vs 1) SABA dispenses (all-cause mortality HR: 1.20, 95% CI 1.16 to 1.24, p<0.001; COPD-related mortality HR: 1.40, 95% CI 1.34 to 1.46, p<0.001). Patients receiving 6+ (vs 1–2) antibiotic dispenses had 62% (HR: 1.62, 95% CI 1.57 to 1.66, p<0.001) and 43% (HR: 1.43, 95% CI 1.38 to 1.49, p<0.001) higher rates of all-cause and COPD-related mortality, respectively. Patients experiencing 6+ (vs 1–5) OCS burst-days had 27% (HR: 1.27, 95% CI 1.18 to 1.36, p<0.001) and 29% (HR: 1.29, 95% CI 1.19 to 1.40, p<0.001) higher rates of all-cause and COPD-related mortality, respectively. Adjusting for covariates, patients with 2–5 (vs 1) SABA dispenses had higher rates of postexacerbation MACE and CVD death (incidence rate ratio: 1.26, 95% CI 1.16 to 1.36, p<0.001 and 1.27, 95% CI 1.16 to 1.40, p<0.001, respectively).Conclusions One-year COPD reliever or exacerbation management medication history was associated with higher rates of mortality and postexacerbation MACE (SABA specific).